Fetomaternal Outcome in Morbidly Adherent Placenta - Sabreena Abbas, Fouzia Shaikh, Nabila Hasan, Sadaf (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the fetomaternal outcome in morbidly adherent placenta Study design: Cross-sectional study. Place and duration of study: Department of Obstetrics & Gynecology, Liaquat University Hospital Hyderabad from 1st January 2022 to 30th June 2022. Methodology: Forty five females of adherent placenta were enrolled. The consent was taken from every relevant patient having low lying placenta with previous scar/surgery the following details were collected. The operative events were recorded. Results: The mean age was 30.77 years and mean gestational age was 34.15 weeks. Majority of the cases 53.3% had history of three previous C-sections, 64.4% cases had placenta accreta, 20% had placenta percreta and 15.6% had p Placenta increta. Antepartum haemorrhage was seen in 68.9% of the cases. 55.6% females underwent C-sections, 22.2% were admitted in ICU, rate of the hysterectomy was high, 46.7% one patient was died. Considering the fetal outcome, 22.2% of the cases had fetal growth retardation, pre-term birth rate was 66.7%, neonatal ICU admission rate was 31.1% of the cases, respiratory distress was seen in 6.7% of the cases, perinatal sepsis was in 11.1% of the cases and intra uterine death rate was 8.9% of the cases. Conclusion: Morbidly adherent placenta was found to be a significant cause of adverse fetal and maternal outcome. It was frequently more prevalent among females who had previous history of scar. Key words: Invasive placenta, Fetomaternal complications